Effect of odontoplasty on apparent digestibility and consumption time of diet for equines - F.C.D. Araújo; M.G. Cruz; J.C.C. Balieiro; M.L. Menezes; C.G. Moreira; C. Giunco; G.F. Correa; R.A. Brandi (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to investigate the effect of odontoplasty on apparent digestibility of diet for horses, consumption time, and particle size of feces. Nine horses were used, aged 14.5±3.3 years and weightng 531±38.7kg. The diet consisted of 1.5% of live weight (LW) in Tifton 85 hay and 0.75% of LW in concentrate for both assays. The experiment consisted of two tests of apparent digestibility using the method of total collection, before and after the odontoplasty, where the consumption time of hay and concentrate was also evaluated and the particle size of the feces was analyzed. An effect (P<0.05) of odontoplasty on the apparent digestibility coefficients of dry matter, organic matter, crude protein, neutral detergent fiber and acid detergent fiber was observed. Effect of the consumption time for the concentrate (P<0.05) was observed, but not for the forage (P<0.05). There was more retention (P<0.05) of the fecal particles in the sieves of bigger granulometry. The odontoplasty increases the digestibility of dietary nutrients and feces particle size, without changing feces quality. Animals after the procedure have shorter concentrate consumption time.